1986
DOI: 10.1530/acta.0.1110151
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of pituitary hGH to GRH1-44 in juveniles with obesity

Abstract: The response of plasma hGH to an iv bolus injection of GRH1-44 (1 \g=m\g/kg) was studied in 14 obese juveniles with a mean overweight of 4.7 \ m=+-\0.05 standard deviation score (sds). Two patterns of response were observed: in all 7 adolescents with 'simple' obesity not related to any particular disorder (group A) the response was good (a mean of 11.8 \ m=+-\2.4 ng/ml) whereas in 6 of the 7 juveniles suffering from syndromes associated with obesity (group B) the response was poor (a mean of 3.2 \m=+-\1.4 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
9
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
(10 reference statements)
3
9
0
Order By: Relevance
“…The blunted GH response to a single bolus injec¬ tion of GHRH, as shown in this study, confirms previous reports (Pertzelan et al 1986;Pintor et al 1986;Loche et al 1987), and, as previously ob¬ served (Loche et al 1987;Rosskamp et al 1987), this blunted response was associated with high im¬ munoreactive Sm-C levels. A tendency to high Sm-C levels in obese prepubertal children associ¬ ated with reduced 24-hour GH secretion has also recently been reported by Minuto et al (1988).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The blunted GH response to a single bolus injec¬ tion of GHRH, as shown in this study, confirms previous reports (Pertzelan et al 1986;Pintor et al 1986;Loche et al 1987), and, as previously ob¬ served (Loche et al 1987;Rosskamp et al 1987), this blunted response was associated with high im¬ munoreactive Sm-C levels. A tendency to high Sm-C levels in obese prepubertal children associ¬ ated with reduced 24-hour GH secretion has also recently been reported by Minuto et al (1988).…”
Section: Discussionsupporting
confidence: 92%
“…Reduced GH responses to a wide variety of stimuii (see Glass et al 1981 for review), inciuding GHRH (Williams et al 1984;Kopelman et al 1985;Pertzelan et al 1986;Pintor et al 1986) is a characteristic feature of obese subjects. We (Loche et af.…”
mentioning
confidence: 99%
“…Both spontaneous as well as stimulated GH secretion is reduced in obese children [31,32] and augmented dur ing starvation [33], while inverse changes are seen in serum IGF-I [34,35], At the cellular level, GH acutely down-regulates GH receptors in liver [36], whereas chronic administration augments hepatic GH binding [37] . The influence of nutrition on serum GHBP is likely to involve other hormonal mediators.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that these patients have decreased GH responses to GH-releasing hormone (9)(10)(11)(12)(13)(14). This could be due to reduced pituitary sensitivity to GHRH, excess of hypothalamic somatostatin, or a chronic state of GHRH deficiency.…”
mentioning
confidence: 99%